2014
DOI: 10.1002/cncy.21398
|View full text |Cite
|
Sign up to set email alerts
|

mRNA and miRNA analyses in cytologically positive endobronchial ultrasound‐guided transbronchial needle aspiration: Implications for molecular staging in lung cancer patients

Abstract: BACKGROUND: Lung cancer is highly aggressive and tends to metastasize early. Therefore, accurate mediastinal staging is important for therapeutic decision making. Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) has emerged as a minimally invasive procedure for mediastinal lymph node sampling and cancer staging. Classical EBUS-TBNA cytology has been combined with molecular staging techniques to improve sensitivity and specificity. This study aimed to assess mRNA integrity in samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…miRNAs are single-stranded, endogenous, non-coding small molecule RNAs, the functions of which have become clearer in recent years. It is highly conserved in structure, and may alter this by specific binding to the target mRNA at the 3'-untranslated region, promoting the degradation of the target gene mRNA or inhibiting its translation and transcription, and therefore regulating target protein expression (15)(16)(17). Previous studies have demonstrated that numerous miRNAs are located in chromosomal regions of the tumor-associated genomes, which possess different functions and serve different regulatory roles in the malignant biological behaviors of tumor cells, particularly proliferation, invasion and metastasis (1).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are single-stranded, endogenous, non-coding small molecule RNAs, the functions of which have become clearer in recent years. It is highly conserved in structure, and may alter this by specific binding to the target mRNA at the 3'-untranslated region, promoting the degradation of the target gene mRNA or inhibiting its translation and transcription, and therefore regulating target protein expression (15)(16)(17). Previous studies have demonstrated that numerous miRNAs are located in chromosomal regions of the tumor-associated genomes, which possess different functions and serve different regulatory roles in the malignant biological behaviors of tumor cells, particularly proliferation, invasion and metastasis (1).…”
Section: Discussionmentioning
confidence: 99%
“…Relative miR-200c expression showed similar tendencies for both types of sample and was ultimately deemed the best classifier in this study. The candidate miRNAs were selected based on the results of a previous study [15], but it has also been reported that miR-200c is highly expressed in metastatic lymph nodes [24]. However, the previous study did not examine the diagnostic yield of miR-200c as a classifying biomarker for detecting metastatic lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Although mRNA has also been shown to be detectable in the plasma of cancer patients [98], the stability of miRNAs has been shown to be superior as compared to mRNAs, making laboratory diagnosis more feasible [99]. Circulating cellfree miRNAs may be derived from metastasizing cells originated from primary tumor mass or they are leaked from the tumor mass itself.…”
Section: Micrornasmentioning
confidence: 99%